A Hierarchical Optimization Framework for Peer-To-Peer Energy Trading in Medium- and Low-Voltage Distribution Networks - Garcia-Munoz, F (IEEE Computer Society, 2025)
This paper introduces a new hierarchical optimization framework for coordinating peer-to-peer (P2P) energy trading among users in medium-voltage (MV) and low-voltage (LV) distribution networks. The framework models LV networks as energy communities (ECs) with distributed energy resources (DERs), where community members trade energy internally and with external communities via the MV-LV interface. The MV network, which also integrates DERs, establishes operational strategies for inter-EC energy transactions and efficiently allocates resources to meet the energy demand of the ECs. The optimization models are based on the second-order cone relaxation to consider network restrictions and assume an operation within a day-ahead market structure. Thus, the proposed bilevel optimization model adopts an EC-center approach, with the LV networks acting as multiple leaders at the first level, where the ECs establish the energy requirements, and the second level is represented by the MV network, which adjusts its resource dispatch to ask the energy demand efficiently. The IEEE 33-bus system and a modified version of the IEEE 906-bus systems are used to represent the MV and the LV networks, respectively, and to test the algorithm. Simulation results demonstrate the algorithm s effectiveness in optimizing energy flows, balancing community needs, and complying with network constraints. © 2025 IEEE.